Individual Perception of Ethical Behavior and Whistleblowing on Fraud Detection through Self-Efficacy - I Gusti Ayu Purnamawati (University of Merdeka Malang, 2018)
This study aims to determine individual perceptions of ethical behavior and whistleblowing on fraud detection through self-efficacy. Study on banking sector in Bali Province. This study uses a quantitative approach. Sampling method using simple random sampling method, with the number of samples that is 70 respondents. Whistleblowers are employees and or stakeholders who see some wrong actions can be independent and without published report the action to the company's management without fear of mutual action. The type of data in this study is primary data. The data were collected by using questionnaires. Measurement using Likert scale. Analysis of research data using hierarchical regression analysis model. The results showed: (1) individual perceptions about ethical behavior have no effect on fraud detection; (2) whistleblowing and self-efficacy have a positive and significant effect on fraud detection; (3) self-efficacy does not succeed in moderating the relationship between individual perceptions of ethical behavior toward fraud detection; and (4) self-efficacy does not moderate the relationship between whistleblowing to fraud detection.JEL Classification: M51; O15DOI: https://doi.org/10.26905/jkdp.v22i2.1991